Kolusi dan Nepotisme dalam Perspektif al-Qur'an (Studi Pendekatan Tafsir Tematik) - - Rahman; Imam Ghozali (STAIN Bengkalis, 2018)
Nowadays, collusion and nepotism are considered as the worst indicator of moral decline in social life in our country. That behaviours are product of inhuman social-politic and economic relation. It was the principle of justice violation, and the continuity in doing that violation by moslem people would cause disaster. Therefore manipulation and misapplication of power and authority usually begin from bad attitude of certain community that effects moral degradation in various of life aspects, it intimidates right and obligation equality and covers the value of justice that encouraged by the al-Quran and as-Sunnah.___________________Keywords: Collusion, Nepotism, al-Quran.